Brain and Emotion. (January 2018) - Kagan, Jerome
Progress in understanding the relation between brain profiles and emotions is being slowed by the belief in a collection of basic emotional states, with the names: fear, anger, joy, disgust, and sadness, that do not specify the species or age of the experiencing agent, the origin of the state, or the evidence used to infer it. This article evaluates critically the premise that decontextualized emotional words refer to natural kinds. It also suggests that investigators set aside the currently popular words and search for relations, in humans and animals, between patterns of measures to varied incentives presented in distinctive contexts.